ภาวะหมดไฟในการทำงาน และปัจจัยที่เกี่ยวข้องของพนักงานบริษัทเอกชนที่ดำเนินธุรกิจจัดจำหน่ายวัสดุก่อสร้างแห่งหนึ่ง - สโรชาพัชร์ เตชโรจนกัญจน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2021)
The purpose of this descriptive study was to explore the level of job burnout and related factors among employees of a private distribution company in building materials business. A cross-sectional study was conducted on 331 employees of a private distribution company in the building materials business from January 2022 to April 2022. The data was collected by an online survey using a demographic and a work-related questionnaire, WHOQOL-BREF-THAI, r-Thai-MSPSS, and MBI-GS in Thai version. Chi-square test was applied to determine the association between factors and job burnout. Logistic regression was used to identify the predictors of job burnout in the participants.The study found the high level of job burnout among participants in each dimension, emotional exhaustion was 46.2%, cynicism was 48.9%, and professional efficacy was 45.9%. The quality of life was in moderate level (75.8%) and the social support was in high level (61.6%). The factors related to emotional exhaustion and cynicism were age, marital status, children, income, economic status, exercise, work experience, work position, work commute, working hours, and workload. A type of residence, family burden, hour of sleep, and commute time were the factors that related to emotional exhaustion. An education level and benefit were the related factors in cynicism. The quality of life and social support were related to job burnout in all domains. The predictive factors of high level in job burnout in emotional exhaustion and cynicism domain were 1-10 years of work experience, non-management level, and heavy workload. The long working hour (> 8 hours/day) was a predictive factor in emotional exhaustion domain. Low-moderate level of QOL was a predictive factor to job burnout in all dimensions. Low-moderate level of social support was a predictive factor of job burnout in cynicism and professional efficacy domain. The results could raise awareness in the organization for the preventive and protective solutions to reduce employee job burnout effectively.